An application of debt Laffer curve: Empirical evidence for Romania's case - Ştefania Tatu (Romanian Journal of Fiscal Policy (RJFP), 2014)
The recent economic and financial crisis emphasized the vulnerabilities at international level and among them is the public debt. The aim of this paper is to analyse the debt Laffer curve for Romania's case to see if country suffer from debt overhang. Data on public debt for the period 2013 - 2014 showed that Romania is on the right side of the debt Laffer curve, far from the peak of debt beyond which we can talk about a shift on the wrong side of the curve.
Keywords: H63; G15; E62; 330; Laffer curve; public debt; economic crisis; fiscal policy